Parameter analisis voltammetri pulsa diferensial elektrode grafit pensil untuk penentuan kadmium - Marlina Karundeng; Yenni Wahyuni Hartati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Cadmium (Cd) is one of the most important non-essential heavy metals, but can continue to increase in the environment. Bioaccumulative cadmium poisoning may cause kidney disease, stomach disorders, brittle bones, haemoglobin decline, and tooth pigmentation. Therefore, an analytical method for determining cadmium content should be developed. Methods for the determination of cadmium metal content that has been widely used is the method of AAS and ICP-AES method. With comparable sensitivity and selectivity, electrochemical methods such as voltammetry have been widely used as an interesting method for determining cadmium content, the instrumentation in this method is simpler than that of AAS and ICP-AES. The purpose of this study was to develop a method of voltammetry in determining cadmium using graphite pencil as a working electrode and parameter analysis of this method for cadmium quantification. The results of this study indicate that the voltammetric method using graphite pencil electrode can detect cadmium (II), with detection limit of 0.8 ppm, quantification limit of 2.8 ppm, linearity range from 2.8 to 4.8 ppm, and an accuracy of 0.21 -0.58%.